"Sandwich Deformity" in Klippel-Feil syndrome: A "Full-Spectrum" presentation of associated craniovertebral junction abnormalities. (July 2018) - Tian, Yinglun; Fan, Dongwei; Xu, Nanfang; Wang, Shenglin
Highlights: "Sandwich Deformity" means the patients with C2/3 fusion and C1 occipitalization meantime. CVJ abnormalities may all be part of the same pathological process initiated by cervical vertebrae fusion in KFS. The syringomyelia could be formed because of disturbing the normal cerebrospinal fluid circulation. Abstract: Klippel-Feil syndrome (KFS) is defined as congenital fusion of two or more cervical vertebrae resulting from a segmentation failure in the developing spine. According to Samartzis et al., the most commonly fused segments are found at C2/3 (74.1%) and C6/7 (70.4%). In patients with C2/3 fusion, especially when there is additional C1 occipitalization, several secondary anomalies including atlantoaxial dislocation (AAD), basilar invagination (BI), Chiari malformation, and syringomyelia can be identified. In this report, we present a case of a 12-year-old patient with C2/3 and occipitalization and a "Full-Spectrum" presentation of associated CVJ abnormalities including C0/1 fusion, AAD, BI, Chiari malformation, syringomyelia, myelopathy and cranial neuropathy received neurological decompression of the cervico-medullary junction by posterior reduction of the AAD and reconstruction of her CVJ using an unconventional hybrid construct due to a high-riding right vertebral artery in C2. To our knowledge, her "Full-Spectrum" presentation may include the most categories of concomitant abnormalities in the literature. In addition, She received neurological decompression of the cervico-medullary junction using an unconventional hybrid construct due to a high-riding vertebral artery in C2. Three months after the surgery, all of her symptoms recovered significantly. Neither Chiari malformation nor syringomyelia could be identified by MRI two years after the surgery. At the last follow-up (4 years), the patient became completely asymptomatic.